Perioperative factors associated with favorable outcomes of posterior decompression and instrumented fusion for cervical ossification of the posterior longitudinal ligament: A retrospective multicenter study. (November 2018) - Katsumi, Keiichi; Hirano, Toru; Watanabe, Kei; Ohashi, Masayuki; Shoji, Hirokazu; Mizouchi, Tatsuki; Yamazaki, Akiyoshi; Izumi, Tomohiro; Sawakami, Kimihiko; Denda, Hiroshi; Takahashi, Kazuo; Endo, Naoto
Highlights: Perioperative factors associated with favorable outcomes of PDF for cervical OPLL. OPLL patients with preoperative lordotic alignment can have favorable outcomes. It is important to maintain the cervical lordotic alignment postoperatively. Abstract: Purpose: Posterior decompression with instrumented fusion (PDF) is a suitable surgical treatment for K-line (−)-type cervical ossification of the posterior longitudinal ligament (OPLL). However, the adequate indications of PDF have not been clarified yet. The purpose of this study was to investigate the surgical results of PDF and perioperative factors that influence the surgical outcome, and to clarify the adequate indications of PDF. Methods: Twenty-seven patients (21 men and 6 women, mean age: 61.4 years) who were diagnosed with a K-line (−)-type OPLL that was treated with PDF were included in this study. We evaluated these patients clinically and radiologically to investigate the outcomes of PDF and perioperative factors that influence improvements in the Japanese Orthopedic Association (JOA) score. Results: The mean recovery rate of JOA score at the final follow-up examination was 53.3%. In the statistical analysis, the preoperative C2-C7 angle and the C2-C7 angle immediately postoperatively significantly predicted the surgical outcome. The C2-C7 angle immediately postoperatively was the only most important predictor. Using a receiver operating characteristic curve analysis, we found that the cutoff value of the C2-C7 angle immediately postoperatively for good outcomes (recovery rate of JOA score ≥50%) was −2.0°. Conclusions: PDF for K-line (−)-type OPLL patients with preoperative lordotic alignment can be expected to have favorable outcomes, which is the adequate indication for PDF. Since the C2-C7 angle immediately postoperatively was the most important predictor, the physician should pay attention to maintain the cervical lordotic alignment to enhance the surgical outcomes in surgical planning.